Sumanene derivatives functionalized at the internal carbon. Issue 4 (8th December 2016) - Ngamsomprasert, Niti; Dang, Jing-Shuang; Higashibayashi, Shuhei; Yakiyama, Yumi; Sakurai, Hidehiro
Abstract : The first internal functionalization of sumanene. Abstract : The first sumanene derivatives functionalized at the convex face of the internal carbon were reported. The structure of racemic hydroxysumanenone was confirmed by X-ray crystal analysis. The obtained structure was composed of the single enantiomer.